Challenges in Developing and Implementing Rehabilitation Modules in Prisons for Person Convicted for Syariah Offences: (Cabaran dalam Usaha Membangunkan dan Melaksanakan Modul Pemulihan dalam Penjara untuk Pesalah Jenayah Syariah) (Kanun: Jurnal Undang-undang Malaysia, 2015)
This article presents the experience of developing and implementing rehabilitation modules in prisons. Reference is made to documents and activities relating to rehabilitation modules and observations of the implementation of such modules. Information from the statistics unit of the Prisons Department of Malaysia is also referred to. Reference to rehabilitation programmes conducted by the Prisons Department of Malaysia will reveal the planning of activities related to the treatment and rehabilitation of the inmates' physical, mental, attitudinal, moral and spiritual aspects. The development of the modules takes into account education and guidance for shariah offenders.Keywords: prison, offenders, rehabilitation modules, shariah courts